Pengaruh Sistem Pengendalian Intern dan Asimetri Informasi terhadap Kecurangan (fraud) Laporan Keuangan pada Kantor Pusat PT Bank Sulselbar Makassar - Muhammad, Irsad; Wintari Pratiwi, Resi; Yusuf, Marwah (Insan Cita Bongaya Research Journal, 2022)
This research aims to determine whether the system of internal control and fraud information asymmetry affect the financial statements of PT Bank Sulselbar Makassar. Collecting data using primary data obtained from questionnaires using sampling techniques nonprobability (saturated sample). The population is 50 employees, and samples taken 50 respondents. Methods of data analysis using multiple linear regression techniques.The results of this study indicate that the internal control system and significant negative effect, and the information asymmetry influence positively and significantly